2004
DOI: 10.1021/je0498098
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Methane Hydrate Formed from Sodium Dodecyl Sulfate Solution

Abstract: The thermal conductivity of methane hydrate was measured by means of Gustafsson's transient plane source (TPS) technique. The sample was formed from 99.9 vol % methane gas with a 0.9709 mol·m-3 aqueous sodium dodecyl sulfate (SDS) solution under 6.60 MPa and 273.15 K. The in-situ measurement was performed in the temperature range from (263.06 to 277.87) K, and the thermal conductivity of unimpacted sample was lower than that of the impacted, with values of (0.334 to 0.381) W·m-1·K-1 and (0.564 to 0.587) W·m-1·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 23 publications
2
53
2
1
Order By: Relevance
“…This sequence corresponds to an increase in the size of the guest molecule. Huang and Fan [31] found that the thermal conductivities of sI methane hydrate and sII THF hydrate could differ by about 20 %. These results suggest that the guest molecule can affect the hydrate thermal conductivity.…”
Section: Comparisons Of the Thermal Conductivities Of Hydrates With Dmentioning
confidence: 99%
“…This sequence corresponds to an increase in the size of the guest molecule. Huang and Fan [31] found that the thermal conductivities of sI methane hydrate and sII THF hydrate could differ by about 20 %. These results suggest that the guest molecule can affect the hydrate thermal conductivity.…”
Section: Comparisons Of the Thermal Conductivities Of Hydrates With Dmentioning
confidence: 99%
“…As shown in Table, the thermal conductivities of methane hydrate and water differ by <10% at the temperatures found in hydrate-bearing sediments [48,49]. For this reason, firstorder thermal conductivity estimates can neglect the presence of methane hydrate and assume the sediment pore space contains only water [50].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…However, more recent work has been reported by Huang et al [18] and Rosenbaum et al [19] using a commercially available transient plane source (TPS) technique in double-and single-sided configurations, respectively. The original double-sided configuration was developed by Gustaffson [20].…”
Section: Experimental Characterisationmentioning
confidence: 99%
“…The original double-sided configuration was developed by Gustaffson [20]. Considering methane hydrate as an example, the measured values of thermal conductivity for compacted samples at conditions similar to those in natural environments are 0.62 ± 0.02 W/ m·K 3 using a needle probe, and 0.57 [18] and 0.68 ± 0.01 W/m·K [19] using the double-and single-sided TPS techniques, respectively. In the Huang et al study [18], hydrate was formed from methane and water that contained a surfactant to assist hydrate formation, while in the study or Rosenbaum et al, [19] pressurized methane gas was put in contact with ice and followed by repeated cooling and heating cycles to induce hydrate formation, followed by mechanical compaction to reduce the porosity to the lowest possible level.…”
Section: Experimental Characterisationmentioning
confidence: 99%
See 1 more Smart Citation